Application of Image Media in Learning to Write Descriptive Texts for Class VII SMPN - Henisutra Labone; Juniati Juniati; Ulfah Ulfah; Ida Nuraeni; Andi Bismawati (Global Education Journal, 2026)
Indonesian language learning at the junior high school (SMP) level has an important role in developing students' language skills which include listening, speaking, reading, and writing skills. This study aims to describe the application of image media in learning to write descriptive texts and the ability of grade VII students of SMPN Satap Lik Layana Indah to write descriptive texts after using image media. This study uses a qualitative descriptive method. The research subjects consisted of 10 grade VII students. Data collection techniques are carried out through observation, interviews, documentation, questionnaires, and the results of student written products. Data were analyzed using the Miles and Huberman model which included data reduction, data presentation, and conclusion drawn. The results of the study show that the application of image media is carried out through the activity of observing images, identifying objects contained in images, compiling main ideas, and then developing these ideas into the form of descriptive text. The use of image media helps students understand the object to be described so that it is easier to pour ideas into writing. Students' responses to the use of image media also showed positive results. Students look more active, enthusiastic, and motivated during the learning process. Students' ability to write descriptive texts has improved after the application of image media. Before the application of image media, the highest score of students was 80, and the lowest score was 9, After the application of image media, the highest score increased to 100, and the lowest score became 45, The results of students' writing also showed an improvement in aspects of content, organization, use of vocabulary, and the accuracy of the use of language rules. Of the 10 students who were the subjects of the study, 7 students obtained a score of ≥75 (complete) and 3 students were still under the KKM.